Cobalt-Iron red-ox behavior in nano-structured La0.4Sr0.6Co0.8Fe0.2O3-delta cathodes - Soldati, Analía Leticia (2013)
Nano-sized La0.4Sr0.6Co0.8Fe0.2O3−δ (LSCF) perovskite samples (prepared by a conventional acetate route and a novel acetate synthesis with HMTA additives), were tested simulating a red–ox cycle. The crystallography was studied by X-ray Powder Diffraction (XPD) and the changes in the oxidation state of the perovskite B-site were evaluated by synchrotron X-ray Absorption Near Edge Spectroscopy (XANES). After a reducing treatment, LSFC particles show the appearance of a new phase that coexists with the original one. The structural change is accompanied by a Co and Fe formal oxidation states decrease, although Fe remains always closer to 4+ and Co closer to 3+. The treatment produces a B-site valence average reduction from 3.52+ to 3.26+ and the formation of oxygen vacancies. A re-oxidation treatment under O2 rich atmosphere at 800 °C for 10 h shows that the change is reversible and independent of the two chemical methods used to synthesize the LSCF nano-particles.